From Beyond the Pale to the Pale Riders: The Emerging Association of Bacteria with Oral Cancer. (June 2020) - Fitzsimonds, Z.R.; Rodriguez-Hernandez, C.J.; Bagaitkar, J.; Lamont, R.J.
Oral cancer, predominantly oral squamous cell carcinoma (OSCC), is the eighth-most common cancer worldwide, with a 5-y survival rate <50%. There are numerous risk factors for oral cancer, among which periodontal disease is gaining increasing recognition. The creation of a sustained dysbiotic proinflammatory environment by periodontal bacteria may serve to functionally link periodontal disease and oral cancer. Moreover, traditional periodontal pathogens, such as Porphyromonas gingivalis, Fusobacterium nucleatum, and Treponema denticola, are among the species most frequently identified as being enriched in OSCC, and they possess a number of oncogenic properties. These organisms share the ability to attach and invade oral epithelial cells, and from there each undergoes its own unique molecular dialogue with the host epithelium, which ultimately converges on acquired phenotypes associated with cancer, including inhibition of apoptosis, increased proliferation, and activation of epithelial-to-mesenchymal transition leading to increased migration of epithelial cells. Additionally, emerging properties of structured bacterial communities may increase oncogenic potential, and consortia of P. gingivalis and F. nucleatum are synergistically pathogenic within in vivo oral cancer models. Interestingly, however, some species of oral streptococci can antagonize the phenotypes induced by P. gingivalis, indicating functionally specialized roles for bacteria in oncogenic communities. Transcriptomic data support the concept that functional, rather than compositional, properties of oral bacterial communities have more relevance to cancer development. Collectively, the evidence is consistent with a modified polymicrobial synergy and dysbiosis model for bacterial involvement in OSCC, with driver mutations generating a conducive microenvironment on the epithelial boundary, which becomes further dysbiotic by the synergistic action of bacterial communities.